Doubtful Cannon a western story - Boggs, Johnny D. (Waterville, Me. : Thorndike Press, 2008)
Three twelve-year-olds, two notorious gunfighters, a half-crazed albino, and a grieving woman vie for $30,000 in gold coin, buried twenty years ago in treacherous Doubtful Cañon
91096
Keywords: Treasure troves -- New Mexico; Mining camps -- New Mexico; Friendship in children; Children and older people; Outlaws; Large type books; Shakespeare (N.M.); New Mexico; Western stories